Variants in the SCN5A Promoter Associated With Various Arrhythmia Phenotypes. Issue 9 (September 2016) - Yagihara, Nobue; Watanabe, Hiroshi; Barnett, Phil; Duboscq‐Bidot, Laetitia; Thomas, Atack C.; Yang, Ping; Ohno, Seiko; Hasegawa, Kanae; Kuwano, Ryozo; Chatel, Stéphanie; Redon, Richard; Schott, Jean‐Jacques; et al.
Abstract : Background: Mutations in the coding sequence of SCN5A, which encodes the cardiac Na + channel α subunit, have been associated with inherited susceptibility to various arrhythmias. Variable expression of SCN5A is a possible mechanism responsible for this pleiotropic effect; however, it is unknown whether variants in the promoter and regulatory regions of SCN5A also modulate the risk of arrhythmias. Methods and Results: We resequenced the core promoter region of SCN5A and the regulatory regions of SCN5A transcription in 1298 patients with arrhythmia phenotypes (atrial fibrillation, n=444; sinus node dysfunction, n=49; conduction disease, n=133; Brugada syndrome, n=583; and idiopathic ventricular fibrillation, n=89). We identified 26 novel rare variants in the SCN5A promoter in 29 patients affected by various arrhythmias (atrial fibrillation, n=6; sinus node dysfunction, n=1; conduction disease, n=3; Brugada syndrome, n=14; idiopathic ventricular fibrillation, n=5). The frequency of rare variants was higher in patients with arrhythmias than in controls. In the alignment with chromatin immunoprecipitation sequencing data, the majority of variants were located at regions bound by transcription factors. Using a luciferase reporter assay, 6 variants (Brugada syndrome, n=3; idiopathic ventricular fibrillation, n=2; conduction disease, n=1) were functionally characterized, and each displayed decreased promoter activity compared with the wild‐type sequences. We also identified rare variants in the regulatory region that were associated with atrial fibrillation, and the variant decreased promoter activity. Conclusions: Variants in the core promoter region and the transcription regulatory region of SCN5A were identified in multiple arrhythmia phenotypes, consistent with the idea that altered SCN5A transcription levels modulate susceptibility to arrhythmias.